Être mère et en prison au Cameroun - Jeannette Wogaing (Genre, Sexualité et Société)
Prisons are spaces where people are deprived from their freedom and are submitted to rules which reorganize and govern their everyday life. In such a universe, woman, and even more mothers, are called upon to continue playing their roles. Their emotional relationship with their offspring is often reduced to weekly or monthly visits, of varying duration. For these imprisoned women, prison life does not always allow them to cope with their everyday lives as mothers. Following an investigation carried out between August 2011 and February 2017 in two prisons in Cameroon on the basis of observations, interviews and life stories with sixty mothers in imprisonment and four prison staff, the analysis shows (on the one hand) that prisoners whose children are minors have conflicting relationships with their offspring and, (on the other hand) that the inmates live their imprisonment with bitterness, helplessness and unworthiness. Moreover, their lack of freedom and intimacy leads them to be mother differently.